Development and optimization of hardware for delta relaxation enhanced MRI. Issue 4 (11th November 2013) - Harris, Chad T.; Handler, William B.; Araya, Yonathan; Martínez‐Santiesteban, Francisco; Alford, Jamu K.; Dalrymple, Brian; Van Sas, Frank; Chronik, Blaine A.; Scholl, Timothy J.
<x xml:space="preserve">Abstract</x> Purpose Delta relaxation enhanced magnetic resonance (dreMR) imaging requires an auxiliary B0 electromagnet capable of shifting the main magnetic field within a clinical 1.5 Tesla (T) MR system. In this work, the main causes of interaction between an actively shielded, insertable resistive B0 electromagnet and a 1.5T superconducting system are systematically identified and mitigated. Methods The effects of nonideal fabrication of the field‐shifting magnet are taken into consideration through careful measurement during winding and improved accuracy in the design of the associated active shield. The shielding performance of the resultant electromagnet is compared against a previously built system in which the shield design was based on an ideal primary coil model. Hardware and software approaches implemented to eliminate residual image artifacts are presented in detail. Results The eddy currents produced by the newly constructed dreMR system are shown to have a significantly smaller "long‐time‐constant" component, consistent with the hypothesis that less energy is deposited into the cryostat of the MR system. Conclusion With active compensation, the dreMR imaging system is capable of 0.22T field shifts within a clinical 1.5T MRI with no significant residual eddy‐current fields. Magn Reson Med 72:1182–1190, 2014. © 2013 Wiley Periodicals, Inc.